Modeling forest fire mitigation policy through disaster-aware digital tourism villages to support the green local economy in Riau, Indonesia - M Fajar Anugerah; Mhd Rafi Yahya; Amir Syamsuadi (Otoritas : Jurnal Ilmu Pemerintahan, 2026)
Riau Province has been identified as one of the regions most severely affected by forest and land fires since 2015. This study aims to (1) analyze the implementation of forest and land fire mitigation policies, (2) measure the level of village preparedness in facing forest and land fires, and (3) examine the impact of Disaster-Aware Digital Tourism Villages on local economic empowerment in Riau Province. The study employs a mixed-method approach, combining quantitative and qualitative techniques. This research develops a Disaster Mitigation Policy Model for forest and land fires through a Disaster-Aware Digital Tourism Village framework based on economic empowerment. The analysis includes policy evaluation, assessment of village readiness levels, and measurement of the contribution of disaster-aware digital tourism villages to community economic activities. The results indicate that Riau Governor Regulation Number 9 of 2020 serves as the legal foundation for the Regional Disaster Management Agency in implementing forest and land fire mitigation. Furthermore, the findings demonstrate that the disaster-aware digital tourism villages model contributes to increasing community preparedness levels and supports local economic empowerment through green economy-based activities grounded in local wisdom.